2015
DOI: 10.1007/s11548-015-1224-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D imaging in the real-time US–CT fusion navigation for minimal invasive tumor therapy

Abstract: Experimental results showed that the accuracy of needle targeting can be improved with the guidance of the real-time 3D imaging than that with the guidance of both 2D US images and US-CT fusion images in IG-MIT. Assistant function of 3D imaging is obviously for medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…By calibrating the sensors, probe and MW antenna, the computer acquired and displayed information on real-time position and orientation of the US probe and the MW antenna. The accuracy and methods of calibration were verified in our previous studies [26,[28][29][30].…”
Section: Electromagnetic Tracking Devicementioning
confidence: 65%
See 1 more Smart Citation
“…By calibrating the sensors, probe and MW antenna, the computer acquired and displayed information on real-time position and orientation of the US probe and the MW antenna. The accuracy and methods of calibration were verified in our previous studies [26,[28][29][30].…”
Section: Electromagnetic Tracking Devicementioning
confidence: 65%
“…In previous studies [26][27][28][29][30], our research group developed and presented a 3D navigation software system that was applied to perform relevant experimental studies. These previous studies demonstrated that the navigation software could satisfy the clinical requirements of effectiveness, stability and security.…”
Section: Self-developed 3d Finsmentioning
confidence: 99%
“…Our group developed 3D visualisation preoperative planning software that included tumour segmentation, simulation of ablation volume, access-path planning, and visualisation of both the patient anatomy and planned strategy [14,18]. The imaging data were imported into the EFILM software and were analysed by the 3D visualisation platform.…”
Section: D Visualisation Operative Treatment Planning and Microwave mentioning
confidence: 99%
“…Traditionally, 2-dimensional imaging can provide valuable information about the anatomical structure, but it lacks the spatial positioning information of volumetric data that clinicians must know for minimally invasive treatment. The results of human error, such as weakness in spatial sense and imperfect hand-eye coordination, often lead to imprecise needle positioning [14]. 3D visualisation preoperative planning can display the location and relationships of the tumour with surrounding tissues, predict the time-temperature profile during ablation, improve surgical skills and the safety of surgery, reduce surgical complications and promote better long-time prognoses [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[45] First, locating tumors using CT/MRI scans and then making an alignment and fusion with real-time ultrasound examination that accomplishes real-time needle biopsy guidance for precise location puncture of isolated tumors, real-time ultrasound imaging can also be used to monitor tumor ablation under fusion imaging mode, which avoids damage to surrounding tissues. [46] Liu et al . [47] showed that all 18 target hepatocellular carcinoma (HCC) nodules could be detected with fusion images in all patients, but could not be detected on conventional ultrasound.…”
Section: Ultrasound-computed Tomography/magnetic Resonance Imaging Fumentioning
confidence: 99%